1989
DOI: 10.1192/bjp.154.6.797
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nicotine on Attention, Information Processing, and Short-Term Memory in Patients with Dementia of the Alzheimer Type

Abstract: Nicotine in patients with dementia of the Alzheimer type (DAT) produced a significant and marked improvement in discriminative sensitivity and reaction times on a computerised test of attention and information processing. Nicotine also improved the ability of DAT patients to detect a flickering light in a critical flicker fusion test. These results suggest that nicotine may be acting on cortical mechanisms involved in visual perception and attention, and support the hypothesis that acetylcholine transmission m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
184
0
6

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(202 citation statements)
references
References 18 publications
12
184
0
6
Order By: Relevance
“…Few studies have shown that nicotine may actually improve short‐term cognitive performance7, 30 and inhibit amyloid formation 31, 32. On the other hand, various other studies have shown that smoking is a risk factor for Alzheimer's disease, namely due to reactive oxygen species produced by smoking 33, 34, 35, 36, 37.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have shown that nicotine may actually improve short‐term cognitive performance7, 30 and inhibit amyloid formation 31, 32. On the other hand, various other studies have shown that smoking is a risk factor for Alzheimer's disease, namely due to reactive oxygen species produced by smoking 33, 34, 35, 36, 37.…”
Section: Discussionmentioning
confidence: 99%
“…As a further measure of mental flexibility, including the ability to alter cognitive sets, the Wisconsin card-sorting test (WCST) 37 was administered and the ratio of perseverative errors to the number of trials administered used in our analysis. Spatial working memory and sustained attention were evaluated by the computerized CANTAB battery, using the spatial working memory (SWM) 38 and rapid visual information processing (RVP) subtests 39 , respectively. Intelligence was evaluated using the Wechsler Abbreviated Scale of Intelligence (WASI-I) 40 .…”
Section: Methodsmentioning
confidence: 99%
“…RVIP, a subtest from the CANTAB battery was used to access vigilance, which is the ability to sustain attention on one or more items over a period of time 39 . The main variable is A9, which is a signal detection measure of sensitivity to errors regardless of error tendency.…”
Section: Methodsmentioning
confidence: 99%
“…In human studies, nicotine improved discriminative sensitivity and reaction times on a computerized test of attention and information processing in AD patients (Sahakian et al, 1989). Other studies showed that nicotine improved attention and memory in patients with AD or Parkinson's disease (Min et al, 2001;Vidal, 1996).…”
Section: Cholinergic Agonistsmentioning
confidence: 95%